Evaluation of the wound healing in full thickness skin autograft with different doses of topical stichopus spj extract in sprague dawley rats - Sulong, Husnaida Abdul Manan (2010)
Gamat refers to a collection of sea cucumbers most commonly consumed as traditional remedies by Malaysians. With its known healing properties to date, the effect of topical gamat extract could be beneficial in the healing process of the skin grafts and the effective dose could be determined. Objectives: The aim of this study was to investigate the effect of topical gamat from the species Stichopus spl at different concentrations (5 %, 10 % and 20 % w/w) on the healing process of skin auto grafts in female Sprague Dawley rats using macroscopic and microscopic parameters respectively. Method: This study was a randomized control trial with parallel design. Animals were randomly divided into control, low dose treated (5 %), medium dose treated (10 %) and high dose treated (20 %) groups. Dorsal full thickness skin sheets (2cm x 2cm) were harvested and were preserved between 6° to go Celsius for 5 days. 0.5 ml of topical substances (control and gamat extracts) was uniformly applied onto the graft wound beds at Day zero and Day five post-harvesting. Skin grafts were autotransplanted at Day five and fixed with 5-0 silk interrupted sutures. Seven days post graft transplantation, the grafts were assessed macroscopically and microscopically. Results: The animal mortality rate observed in this study is 27.6 %. Macroscopic assessment showed that there were no significant difference, in term of graft adherence, graft color and graft pliability between all gamat-treated groups and the controls. Semiquantitative microscopic assessment revealed that there were no significant difference in the infiltration of inflammatory cells (neutrophils, macrophages) and proliferation of fibroblasts and new blood vessels of the grafts between gamat-treated animals and the controls. However, there was a significant difference in term of graft plane separation between the controls and the medium dose treated group (10 %) (P<O.OOS). In all groups, the body weight showed significantly difference with declining pattern from Day zero to Day fivr post-harvesting (P<O.OS). There were no significant differences within groups seen from Day six to Day twelve. Cmrclusion: Application of Stich opus sp 1 extract (1 0 % w/w) seemed to hasten the acceptance of the skin graft by the wound bed, as demonstrated by the reduction of the plane separation following the application of the extract. Therefore, Stichopus spl extract does have an effect on the healing process of skin auto grafts in Sprague Dawley rats.